2017
DOI: 10.1161/hypertensionaha.116.08175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Kidney Function Because of Living Kidney Donation on Left Ventricular Mass

Abstract: The online-only Data Supplement is available with this article at http://hyper.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Altmann et al . also showed increased left ventricular mass after 1 year while Kasiske et al . demonstrated that uric acid and PTH was increased 3 years after nephrectomy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Altmann et al . also showed increased left ventricular mass after 1 year while Kasiske et al . demonstrated that uric acid and PTH was increased 3 years after nephrectomy.…”
Section: Discussionmentioning
confidence: 90%
“…Three different studies have addressed different surrogate markers for cardiovascular disease after kidney donation . In these studies the donors were normotensive at the time of nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because there is no renal cortical damage or ischemia in kidney donors; the circulating renin-angiotensin system is probably not activated. 4 , 5 This lack of association between living kidney donors and increased risk of HTN benefits studies investigating the influence of a reduced GFR on the cardiovascular system as it eliminates the possible confounding effects of high blood pressure. The caveat, however, is that if blood pressure is a major distinguishing feature between donors and patients with chronic kidney disease, findings in kidney donors may not apply to those with CKD.…”
Section: Vascular Changesmentioning
confidence: 99%
“…Detailed studies of donors show small but significant structural and functional changes in the cardiovascular system at 1 year after nephrectomy. 4 , 5 In addition, a single but carefully designed study appears to show a late rise in adverse cardiovascular events. 6 Studies of living kidney donors appear to be a good approach to disentangling the complex association of renal and cardiovascular disease allowing important pathophysiological information on the mechanisms of the association of chronic kidney disease (CKD) and cardiovascular disease to be gained.…”
Section: Introductionmentioning
confidence: 99%